Proper management of clothing used by family careers of patients in insulation environments - Sales Melo, Rosiane; Sá Bezerra Guerreiro, Thayanne; Brito Albuquerque de Oliveira, Priscila; Arraes Pedrosa Barreto, Antônio Salles; Pimentel Assis, Ronny; Pimentel de Carvalho, Sergio; Campos Reinalde, Ana Maria; Azevedo Braga, Alessandra; Portela de Azevedo, Arimatéia (Revista Feridas, 2022)
Introduction: Family caregivers are likely to take microorganisms home through clothes used in the hospital environment. Therefore, to avoid cross-contamination, it is necessary to correctly perform the hygiene/washing of clothes used in the hospital environment, which includes care such as: correct packaging, storage and transport. Objective: To describe the result of the application of guidelines on the management of clothing used by companions of patients hospitalized in isolation environments of a reference hospital in infectology as an aid in breaking the chain of transmission of microorganisms. Methodology: This was a descriptive, prospective study with a quantitative approach. Results: Forty family caregivers of patients in isolation were interviewed, of which 82.5% had never received guidance on the proper handling of clothing used in the hospital environment, 42.9% had already spent one day to five years with the hospitalized patient. , of the total 80% were the patient’s mothers aged between 40 and 60 years and 25% were from the interior of the state and did not exchange and those who informed that they did, 35% reported that they stayed up to 7 days without any family member showing up for make the switch. Conclusion: Therefore, through this study, we realize the need to update the guidelines regarding the processing of clothing used in health services, focusing on the control and prevention of risks associated with this activity.